2020
DOI: 10.1029/2018jf004873
|View full text |Cite
|
Sign up to set email alerts
|

Future Evolution of Greenland's Marine‐Terminating Outlet Glaciers

Abstract: Mass loss from the Greenland ice sheet (GrIS) has increased over the last two decades in response to changes in global climate, motivating the scientific community to question how the GrIS will contribute to sea‐level rise on timescales that are relevant to coastal communities. Observations also indicate that the impact of a melting GrIS extends beyond sea‐level rise, including changes to ocean properties and circulation, nutrient and sediment cycling, and ecosystem function. Unfortunately, despite the rapid g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 295 publications
0
68
0
Order By: Relevance
“…To understand potential impacts of increased melting and discharge on coastal ecosystems, we need to understand the time scales of change at Greenland's calving fronts (e.g., Catania et al, 2020). Many of Greenland's tidewater glaciers rest on prograde slopes (the bed shallowing inland, Millan et al, 2018), such as Mogens Heinesen in SE Greenland and Savissuaq Glacier in NW Greenland (Morlighem et al, 2017).…”
Section: Call For Further Observationsmentioning
confidence: 99%
“…To understand potential impacts of increased melting and discharge on coastal ecosystems, we need to understand the time scales of change at Greenland's calving fronts (e.g., Catania et al, 2020). Many of Greenland's tidewater glaciers rest on prograde slopes (the bed shallowing inland, Millan et al, 2018), such as Mogens Heinesen in SE Greenland and Savissuaq Glacier in NW Greenland (Morlighem et al, 2017).…”
Section: Call For Further Observationsmentioning
confidence: 99%
“…Over the past decades, liquid runoff from Greenland has increased (Mernild and Liston, 2012;Bamber et al, 2018;Trusel et al, 2018;Perner et al, 2019). When that runoff leaves the ice sheet and enters fjords and coastal seas, it influences a wide range of physical (Straneo et al, 2011;An et al, 2012;Mortensen et al, 2013;Bendtsen et al, 2015;Cowton et al, 2015;Mankoff et al, 2016;Fried et al, 2019;Cowton et al, 2019;Beckmann et al, 2019), chemical (Kanna et al, 2018;Balmonte et al, 2019), and biological (Kamenos et al, 2012;Kanna et al, 2018;Balmonte et al, 2019) systems (Catania et al, 2019). The scale of impacts ranges from the ice-ocean boundary to the distal open ocean (Gillard et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The scale of impacts ranges from the ice-ocean boundary to the distal open ocean (Gillard et al, 2016). The influence of freshwater on multiple domains and disciplines (Catania et al, 2019) is the reason several past studies have estimated runoff at various 15 km resolution) and the Regional Atmospheric Climate Model (RACMO; Noël et al (2019), 5.5 km resolution) and runoff, R, is defined by…”
Section: Introductionmentioning
confidence: 99%
“…This strategy could be expanded by calculating terminus positions along additional flowlines. In contrast, the box method (Walsh et al, 2012;Moon and Joughin, 2008;McNabb and Hock, 2014;Catania et al, 2020) evaluates terminus change in terms of a single area change value. shows the median misfits between the automated and manual delineations by image condition for both the 10% (52 out of the 512 − see section 2.5.2) of manual delineations excluded from the optimization algorithm development and the full manual dataset.…”
Section: Identification Of Prospective Terminus Chainsmentioning
confidence: 99%
“…The marine-terminating glaciers in southeast Greenland, particularly, have been observed to undergo rapid retreat in response to oceanic forcing (Seale et al, 2011;Howat et al, 2008;Howat and Eddy, 2011;Walsh et al, 2012;Sole et al, 2011). From 2001-2005, Seale et al (2011 observed synchronous retreat in marine-terminating glaciers south of 69 and potentially vary between glaciers, subsurface ocean warming increases terminus undercutting caused by submarine melting and reduces resistance to ice flow provided by sea ice and icebergs adjacent to the terminus, resulting in increased rates of ice discharge at glacier calving fronts (Benn et al, 2007;Straneo et al, 2012;Catania et al, 2020). Surface melting also contributes to undercutting when it is routed underneath the glacier (as subglacial discharge) and discharged at the glacier's grounding line (Fried et al, 2018;Slater et al, 2018).…”
Section: Introductionmentioning
confidence: 99%